ANALISIS KEPUTUSAN PEMBELIAN KONSUMEN DIPENGARUHI GREEN MARKETING PRODUK - Ahmad Nurdin Hasibuan; Prisila Damayanti; Rudi Laksono (Jurnal Manajemen dan Bisnis, 2021)
This study aims to determine the effect of being biodegradable (Biodegradable), recyclable (Recyclable), resource reduction (Source Reduction), Ozone Safe Ozone Friendly (OzoneSafe and OzoneFriendly), and reuse (Reuse) on product purchasing decisions. PT Indofood Sukses Makmur Tbk. The research sample used was 114 respondents. Determination of the sample used quota sampling and the type of data using primary data. Multiple linear regression was used as an analytical tool. The results showed that Biodegradable had a positive value, had a significant effect with = 0.000. Furthermore, Recyclable has a positive value, has no significant effect with = 0.528. Source Reduction is positive, has no significant effect on alpha (α) of 0.934. OzoneSafe and OzoneFriendly have positive values, no significant effect on alpha (α) of 0.875. Reuse is positive, has no significant effect on alpha (α) of 0.601. The simultaneous effect of the Fcount value is 177.568, the significance is 0.000 so that there is a significant effect between these independent variables on the purchasing decisions of Indofood products. The determination is 88.7%, the remaining 11.3% is explained by other factors outside the model.